Reflexology : A Practical Approach - Pitman, Vicki; MacKenzie, Kay. (Cheltenham : Nelson Thornes, 2002)
This comprehensive text will be useful for all those studying reflexology. It provides thorough information for all reflexology courses. It includes a full colour chart, diagrams and interactive exercises.
Previous ed.: Cheltenham: Stanley Thornes, 1997.
Fold out chart on back cover.
Includes bibliographical references (p. 268-269) and index.
Keywords: Reflexology (Therapy); Reflexology (Therapy) -- Problems, exercises, etc; Health and Fitness